Pengaruh Brand Image dan Cita Rasa terhadap Keputusan Pembelian Melalui Minat Beli pada Richeese Factory Golden City Kota Bekasi - Nurul Cahyani; Hadita Hadita; Neng Siti Komariah; Dewi Puspaningtyas Faeni; Yayan Hendayana (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
The purpose of this research is to determine the influence on Brand Image and Taste at Richeese Factory on Purchasing Decisions through Purchase Intention. In this research, quantitative research methods were used and un obtaining samples the author used Non-Probability Sampling techniques. The number of samples used in this research was 100 respondents, where the focus of these respondents was consumers of Richeese Factory Golden City, Bekasi City.